Disruptive Behavior dan Bentuk Perlakuan Guru - Annur Aliyyu (Universitas Mathla'ul Anwar Banten, 2019)
DISRUPTIVE BEHAVIOR AND TEACHER TREATMENTS CONFIGURATION. This study aims to determine the theoretical concepts, acceptability, practicability, and effectiveness of guidelines for rational emotive counseling, homework assignment techniques, and confrontation techniques. This research is development research with steps: design preparation, design validation, design testing, and design revision. Questionnaire and interview methods collected data, and the data collected were analyzed using descriptive analysis techniques. The results showed: (1) Theoretically rational emotive counseling procedures homework assignment techniques and confrontation techniques include steps: showing the counselee that the problem faced is related to irrational beliefs, bringing the counselee to the opposite stage of consciousness by showing that the counselee is maintained emotional disturbances to stay active by always thinking illogically, correcting the thoughts of the counselee and leaving irrational ideas, challenging the counselee to develop rational philosophies. The difference between the two lies in the things done at each step; (2) Acceptability of rational emotive counseling guidelines for homework assignment techniques and confrontation techniques; (3) The practicality of rational emotive counseling guidelines for homework assignment techniques and confrontation techniques is very high; (4) The effectiveness of rational emotive counseling guidelines for homework assignment techniques and confrontation techniques is very high.